Respostas
respondido por:
1
x=-2
2.-2+3y=12
-4+3y=12
3y=12+4
3y=16
y=16/3
(-2,16/3)
x=-1
2-1+3y=12
-2+3y=12
3y=12+2
3y=14
y=14/3
(-1,14/3)
x=0
2.0+3y=12
0+3y=12
3y=12
y=12/3
y=4
(0,4)
x=1
2.1+3y=12
2+3y=12
3y=12-2
3y=10
y=10/3
(1,10/3)
x=2
2.2+3y=12
4+3y=12
3y=12-4
3y=8
y=8/3
(2,8/3)
2.-2+3y=12
-4+3y=12
3y=12+4
3y=16
y=16/3
(-2,16/3)
x=-1
2-1+3y=12
-2+3y=12
3y=12+2
3y=14
y=14/3
(-1,14/3)
x=0
2.0+3y=12
0+3y=12
3y=12
y=12/3
y=4
(0,4)
x=1
2.1+3y=12
2+3y=12
3y=12-2
3y=10
y=10/3
(1,10/3)
x=2
2.2+3y=12
4+3y=12
3y=12-4
3y=8
y=8/3
(2,8/3)
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás